FAKTOR KESUKSESAN YANG MEMPENGARUHI PARTISIPASI DAN NILAI PENAWARAN PESERTA LELANG ELEKTRONIK (E-PROCUREMENT) JASA KONSTRUKSI DI KABUPATEN KLUNGKUNG - I Putu Andy Wiranata Wijaya; G.A.P. Candra Dharmayanti; Dewa Ketut Sudarsana (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2019)
THE SUCCESS FACTORS AFFECTING PARTICIPATION AND VALUE OF SUPPLIERS OF ELECTRONIC EQUIPMENT (E-PROCUREMENT) CONSTRUCTION SERVICES IN REGENCY OF KLUNGKUNG ABSTRACT The advantages of e-procurement are ensuring transparency, document security, minimizing printing costs, saving time and money. But over time, in Klungkung District, there are obstacles in the implementation of this e-procurement system, the deadline for short document uploads, the existence of perceived burdensome requirements, and unpreparedness of human resources. These constraints affecting the providers and users of services in implementing this system affect the decline in participation of electronic auction participants in Klungkung Regency. The purpose of this research is to know what factors influence the participation and value of electronic bidding auction of construction service work in Klungkung Regency. The research was conducted in Klungkung Regency. Contractor who became the object of research is a member of Bali Province GAPENSI. Data collection techniques were conducted by questionnaire method. The number of samples was 87 people determined by the slovin method. The analysis used is factor analysis. The factor of contractor support is the dominant factor that influences the participation of electronic construction auction participants in Klungkung Regency with eigen value of 11,467 and total variance of 22,934. The factor of return on investment is the dominant factor affecting the offer value and the electronic auction of construction service in Klungkung Regency with eigenvalue of 11,491 and the total variance is 22,097.